Implementation of Dual Literacy for Educators Through English Language Upskilling and Digital Competence in Integrated Islamic Schools - Saryati Purwanigara; Rusdianah; Nenden Rohmayanti; Supardi US; Hasbullah (Journal of Educational Studies, 2026)
This study analyzes the implementation of dual literacy for educators through English upskilling strategies and digital competence development at SDIT Visi Mulia Islamic School in relation to Permendikdasmen No. 21 of 2025. The study is based on the growing demand for 21st-century education, which requires teachers to possess digital literacy and English proficiency in order to support innovative and globally competitive learning. Dual literacy, consisting of digital literacy and English language competence, has become an essential component in improving teacher professionalism and strengthening students’ global competencies. The research employed a qualitative descriptive approach using a case study design. Data were collected through classroom observations, in-depth interviews, and documentation involving school leaders, teachers, and school management. The findings revealed that the implementation of dual literacy was carried out systematically through digital skills training, English for Teachers programs, bilingual learning practices, and the integration of technology into classroom instruction. Teachers demonstrated increased confidence in using digital tools and English communication in learning activities. Students also showed higher engagement, improved participation in digital-based learning, and greater willingness to use simple English expressions in classroom interaction. However, several challenges were identified, including unequal teacher competencies, limited digital infrastructure, and time constraints for professional development activities. Overall, the study concludes that the successful implementation of dual literacy is strongly influenced by the synergy between government policy, school innovation, and teacher motivation in creating adaptive, innovative, and globally competitive Islamic education.